DEVELOPMENT OF BASIC ENGLISH GRAMMAR LEARNING MATERIALS USING SOCIAL MEDIA PLATFORM YOUTUBE AT SMK NEGERI 2 RANTAU UTARA - Nasution, Ernida; Muhammad Rusli; Harahap, Anna leli (Journal of English Education and Linguistics, 2025)
This study aims to develop effective and engaging basic English grammar learning materials using the YouTube social media platform for eleventh-grade students at SMK Negeri 2 Rantau Utara. The research employed the ADDIE development model, which includes five phases: Analyze, Design, Develop, Implement, and Evaluate. Data collection techniques included expert validation, student questionnaires, and pre-test and post-test assessments. A total of 20 students participated in the trial implementation. The results of media validation showed a feasibility score of 86%, while content validation reached 93%, indicating that both the media and materials are valid for instructional use. Student feedback revealed high practicality, and learning outcome analysis showed significant improvement, with average post-test scores increasing from 75 to 93.2. These findings suggest that integrating YouTube as a learning platform can enhance students’ understanding of basic English grammar and contribute to a more interactive and student-centered learning environment.